Catalytic Reduction of Toxic Nitroarenes in Aqueous Medium Using Worm‐Like Rhodium Nanoparticles. Issue 30 (23rd October 2017) - George, Anu; Selvan, Dhanashree; Mandal, Sukhendu
Abstract: We demonstrate a facile synthesis of worm‐like rhodium nanoparticle stabilized by octadecylamine. This worm‐like nanoparticle exhibits excellent catalytic activity toward the reduction of nitro aromatics in the presence of NaBH4 in aqueous medium at room temperature. The reaction follows pseudo‐first order kinetics with a rate constant of 0.0216 s −1 . We have explored this catalytic activity for the reduction of several nitro derivatives. This catalyst can effectively reduce toxic nitro aromatics in aqueous medium in much faster rate compared to other Rh‐based catalysts. Abstract : We demonstrate the effective removal of toxic nitroaromatics by chemical reduction using worm like rhodium nanoparticles in the presence of sodium borohydride at room temperature. The nanoparticle was synthesized using a wet chemical method, stabilized using amine functionality of octadecylamine. This heterogeneous catalyst can reduce nitroaromatics in aqueous medium in faster rate and requires a very low activation energy following pseudo first order kinetics. Catalysts was reused upto 3 cycles.